First biocompatibility margins for optical stimulation at the eardrum via 532-nm laser pulses in a mouse model - Sorg, Katharina (J Biomed Opt, 2019)
Hearing impairment affects [Formula: see text] million people worldwide. Conservative therapies, such as hearing aids, bone conduction systems, and middle ear implants, do not always sufficiently compensate for this deficit. The optical stimulation is currently under investigation as an alternative stimulation strategy for the activation of the hearing system. To assess the biocompatibility margins of this emerging technology, we established a method applicable in whole-mount preparations of murine tympanic membranes (TM). We irradiated the TM of anesthetized mice with 532-nm laser pulses at an average power of 50, 89, 99, and 125 mW at two different locations of the TM and monitored the hearing function with auditory brainstem responses. Laser-power-dependent negative side effects to the TM were observed at power levels exceeding 89 mW. Although we did not find any significant negative effects of optical stimulation on the hearing function in these mice, based on the histology results further studies are necessary for optimization of the used parameters.